2022
DOI: 10.1002/2211-5463.13486
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of lung cancer induced via intranasal injection for anticancer drug screening and evaluation of pathology

Abstract: The pathologies and lethality of lung cancers are associated with smoking, lifestyle, and genomic factors. Several experimental mouse models of lung cancer, including those induced via intrapulmonary injection and intratracheal injection, have been reported for evaluating the pharmacological effect of drugs. However, these models are not sufficient for evaluating the efficacy of drugs during screening, as these direct injection models ignore the native processes of cancer progression in vivo, resulting in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Additionally, there were clear neoplastic lesions such adenomas, adenocarcinomas, and adenosquamous carcinomas. These findings are consistent with a prior study that found that Ure initiates stage-2 carcinogenesis, and BHT then stimulates the development of started cells (Tanaka et al, 2023).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, there were clear neoplastic lesions such adenomas, adenocarcinomas, and adenosquamous carcinomas. These findings are consistent with a prior study that found that Ure initiates stage-2 carcinogenesis, and BHT then stimulates the development of started cells (Tanaka et al, 2023).…”
Section: Discussionsupporting
confidence: 93%
“…Studies of the miRNA content of circulating tumor EVs, specifically those purified from the circulation or those from other biofluids, have identified unique profiles, which can be associated with their tumor cells of origin [84] . Therefore, it is well perceived that the isolation of tumor EVs from biofluids, followed by the analysis of their miRNA cargos, has the potential to enable the development of non-invasive tumor detection assays for diagnostic and prognostic applications [85][86][87][88][89][90][91] .…”
Section: Introductionmentioning
confidence: 99%
“…In this proof-of-principle study, we sought to explore the potential of utilizing exhaled miRNAs for non-invasive detection of secondary lung cancer in orthotopic animal models. For these analyses, we chose to inoculate a highly metastatic breast cancer cell line that has been well documented to rapidly establish significant pathological lung tumor burden in athymic nude mice, which provided an adequate model to test the collection and analysis of exhaled breath condensates [ 92 95 ] .…”
Section: Introductionmentioning
confidence: 99%